2023
DOI: 10.3390/v15071407
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Drug-Resistant Mutations among HIV-1 Subtype A6 and CRF02_AG in Kazakhstan

Abstract: HIV incidence in Kazakhstan increased by 73% between 2010 and 2020, with an estimated 35,000 people living with HIV (PLHIV) in 2020. The development of antiretroviral drug resistance is a major threat to effective antiretroviral therapy (ART), yet studies on the prevalence of drug resistance in Kazakhstan are sparse. In this study on the molecular epidemiology of HIV in Kazakhstan, we analyzed 968 partial HIV-1 pol sequences that were collected between 2017 and 2020 from PLHIV across all regions of Kazakhstan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This discrepancy may be because most of the viruses in our study belonged to sub‐subtype A6. Previous studies have indicated a disproportionate prevalence of NNRTI DRMs in the A6 sub‐subtype compared with the CRF_02AG subtype [14, 31]. In this subtype, the substitution of a single nucleotide in position 190 can result in the replacement of glycine (G) with serine (S), whereas, in other subtypes, it necessitates a change of two nucleotides [32].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be because most of the viruses in our study belonged to sub‐subtype A6. Previous studies have indicated a disproportionate prevalence of NNRTI DRMs in the A6 sub‐subtype compared with the CRF_02AG subtype [14, 31]. In this subtype, the substitution of a single nucleotide in position 190 can result in the replacement of glycine (G) with serine (S), whereas, in other subtypes, it necessitates a change of two nucleotides [32].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of K103N is primary conditioned by the use of EFV as part of the preferred first-line therapy regimen in Russia [48]. In previous studies, the predominance of K103N among naїve patients infected with CRF63_02A6 and CRF02_AG was noted [49,50].…”
Section: Discussionmentioning
confidence: 99%